Analisis Lingkungan dan Kemampuan Kerja Terhadap Kinerja Pegawai dan Dampaknya Pada Kepuasan Kerja Pegawai (Studi Pada UPTD Puskesmas Muara Komam) - Laili, Noor; Geraldina, Ira; Gunarto, Muji (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to analyze the influence of work environment and workability on employee performance and its impact on employee job satisfaction at UPTD Muara Komam Health Center. The background of this study is based on the importance of employee performance in improving the quality of health services, as well as various problems related to suboptimal work environments and workability conditions. This study integrates the variables of work environment, workability, performance, and job satisfaction in one analysis model to provide a more comprehensive picture of the factors that influence the performance of Puskesmas employees. The research sample consisted of 63 UPTD Muara Komam Health Center employees who were selected randomly. Data collection was carried out through a questionnaire tested for validity and reliability. The data analysis method used was the Structural Equation Model (SEM) with SmartPLS software. The results showed that work environment and workability significantly affected employee performance. Job satisfaction was proven to mediate the relationship between work environment and workability on employee performance. A conducive work environment and good work ability directly improve employee performance and high job satisfaction, further strengthening this relationship. This study provides an important contribution to the development of human resource management policies in the health sector, especially in efforts to improve the performance and job satisfaction of Puskesmas employees. The managerial implications of this study include the need for good work environment management, such as providing adequate facilities and creating harmonious working relationships, as well as improving employee work skills through ongoing training and development programs